The Injectable Woven Bone-Like Hydrogel to Perform Alveolar Ridge Preservation With Adapted Remodeling Performance After Tooth Extraction - Yang, Tao; Xie, Peng; Wu, Zhenzhen; Liao, Yunmao; Chen, Wenchuan; Hao, Zhichao; Wang, Yushu; Zhu, Zhimin; Teng, Wei (Frontiers in Bioengineering and Biotechnology, 2020)
Grafting bone substitute is paramount to prevent the alveolar ridge resorption after tooth extraction and facilitate the subsequent implant treatment. An ideal bone substitute should acquire the excellent osteogenic property, more importantly, possess the suitable remodeling rate in balance with bone formation and desirable clinical manageability. However, none of bone substitute is simultaneously characterized by these features, and currently, the limited remodeling property leads to the excessive waiting time before implantation. Enlightened by woven bone, the transitional tissue that is able to induce osteogenesis during bone healing, could be easily remodeled within a short period and depend on the favorable injectability of hydrogel, an injectable woven bone-like hydrogel (IWBLH) was constructed in this study to address the above problems. To mimic the component and hierarchical structure of woven bone, amorphous calcium phosphate and mineralized collagen fibril was synthesized and compounded with alginate to form IWBLHs with various ratio. Screened by physiochemical characterization and in vitro biological assays, an optimal IWBLH was selected and further explored in rat model of tooth extraction. Compared with the most widely used bone substitute, we showed that IWBLH could be easily handled to fully fill the tooth socket, perform a comparable function to prevent the alveolar bone resorption, and completely remodeled within 4 weeks. This IWBLH stands as a promising candidate for alveolar ridge preservation in future.